Index of microcirculatory resistance-guided therapy with pressure-controlled intermittent coronary sinus occlusion improves coronary microvascular function and reduces infarct size in patients with ST-elevation myocardial infarction: the Oxford Acute Myocardial Infarction - Pressure-controlled Intermittent Coronary Sinus Occlusion study (OxAMI-PICSO study) - De Maria, G; Alkhalil, M; Borlotti, A; Wolfrum, M; Gaughran, L; Dall'Armellina, E; Langrish, J; Lucking, A; Choudhury, R; Kharbanda, R; Channon, K; Banning, A (Europa Digital and Publishing, 2018)
The Oxford Acute Myocardial Infarction PICSO (OxAMI-PICSO) study aimed to assess the efficacy of index of microcirculatory resistance (IMR)-guided therapy with pressure-controlled intermittent coronary sinus occlusion (PICSO) in anterior ST-elevation myocardial infarction (STEMI). Patients with anterior STEMI treated with primary percutaneous coronary intervention (pPCI) were enrolled. Pre-stenting IMR was measured and PICSO treatment delivered if pre-stenting IMR was >40. No PICSO treatment was considered in patients with a pre-stenting IMR ≤40. The control group was derived from a historical cohort of STEMI patients with pre-stenting IMR >40 enrolled in the observational OxAMI study. IMR was measured after completion of pPCI in all patients and within 48 hours in PICSO patients and controls. Cardiac magnetic resonance imaging was performed per protocol for infarct size (IS) assessment within 48 hours after pPCI and at six months. A total of 105 patients were enrolled (25 PICSO, 50 controls with pre-stenting IMR >40, 30 with pre-stenting IMR ≤40). Compared to controls, patients treated with PICSO had a lower IMR at 24-48 hours (24.8 [18.5-35.9] vs. 45.0 [32.0-51.3], p<0.001) and lower IS at six months (26.0% [20.2-30.0] vs. 33.0% [28.0-37.0], p=0.006). An IMR-guided treatment with PICSO in anterior STEMI is feasible and may be associated with reduced IS and improved microvascular function.